In situ chemistry and microbial community compositions in five deep‐sea hydrothermal fluid samples from Irina II in the Logatchev field. (22nd November 2012) - Perner, Mirjam; Gonnella, Giorgio; Hourdez, Stephane; Böhnke, Stefanie; Kurtz, Stefan; Girguis, Peter
Summary We present data on the co‐registered geochemistry (in situ mass spectrometry) and microbiology (pyrosequencing of 16S rRNA genes; V1, V2, V3 regions) in five fluid samples from Irina II in the Logatchev hydrothermal field. Two samples were collected over 24 min from the same spot and further three samples were from spatially distinct locations (20 cm, 3 m and the overlaying plume). Four low‐temperature hydrothermal fluids from the Irina II are composed of the same core bacterial community, namely specific Gammaproteobacteria and Epsilonproteobacteria, which, however, differs in the relative abundance. The microbial composition of the fifth sample (plume) is considerably different. Although a significant correlation between sulfide enrichment and proportions of Sulfurovum (Epsilonproteobacteria) was found, no other significant linkages between abiotic factors, i.e. temperature, hydrogen, methane, sulfide and oxygen, and bacterial lineages were evident. Intriguingly, bacterial community compositions of some time series samples from the same spot were significantly more similar to a sample collected 20 cm away than to each other. Although this finding is based on three single samples only, it provides first hints that single hydrothermal fluid samples collected on a small spatial scale may also reflect unrecognized temporal variability. However, further studies are required to support this hypothesis.